Trends in teaching and learning of mathematical modelling ICTMA14 - Kaiser, Gabriele; Blum, Werner; Ferri, Rita Borromeo; Stillman, Gloria; SpringerLink (Online Service). (Dordrecht Springer Netherlands, 2011)
Applications and modelling and their learning and teaching in school and university have become a prominent topic in the last decades in view of the world-wide importance of the usage of mathematics in science, technology and everyday life. Trends in teaching and learning of mathematical modelling provides the reader ship with an overview on the newest international trends and developments on the teaching and learning of modelling from various theoretical and practical perspectives. The comprehensive overview on the most recent empirical research reflecting the development and promotion of modelling competencies at various age levels allows insight into possible affective and cognitive blockages and barriers for students' modelling processes and its teaching. The papers on the usage of technology describe new possibilities, how the usage of technology can inspire the teaching and learning of modelling. International modelling projects offer chances and possibilities to enrich the teaching and learning of mathematical modelling at secondary and tertiary level and describe challenging modelling examples and their possible usage in school and university. The necessary change of teacher education towards an inclusion of mathematical modelling is reflected from different perspectives and challenging examples are given.The contributing authors are influential members of the group 'International community of teachers of modelling and applications' and important researchers in mathematics and mathematics education. The book will be of interest to mathematics educators, teacher educators, researchers, education administrators, curriculum developers, teachers and student teachers.
Electronic reproduction.
Keywords: Mathematical models -- Congresses; Mathematical models -- Study and teaching -- Congresses; Electronic books